2016
DOI: 10.5194/acp-2016-866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomass burning emissions in north Australia during the early dry season: an overview of the 2014 SAFIRED campaign

Abstract: <p><strong>Abstract.</strong> The SAFIRED (Savannah Fires in the Early Dry Season) campaign took place from 29th of May, 2014 until the 30th June, 2014 at the Australian Tropical Atmospheric Research Station (ATARS) in the Northern Territory, Australia. The purpose of this campaign was to investigate emissions from fires in the early dry season in northern Australia. Measurements were made of biomass burning aerosols, volatile organic compounds, polycyclic aromatic car… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 32 publications
(53 reference statements)
0
31
0
Order By: Relevance
“…These biomass-burning events occur extensively in northern Australia throughout the dry season as the result of natural and accidental lighting, as well as part of local land management practices (RusselSmith et al, 2007). Nelson et al (2009) concluded that burning in the northernmost part of Australia can contribute up An intensive study of these biomass-burning events undertaken at ATARS during the early dry season in 2014 also confirmed spikes in GEM concentration that were associated with biomass burning (Mallet et al, 2016;Desservettaz et al, 2017). The distance to the fire and atmospheric dispersion, as well as vegetation type and associated mercury loading, were all identified as factors influencing the strength of these biomass-burning signals.…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 88%
See 1 more Smart Citation
“…These biomass-burning events occur extensively in northern Australia throughout the dry season as the result of natural and accidental lighting, as well as part of local land management practices (RusselSmith et al, 2007). Nelson et al (2009) concluded that burning in the northernmost part of Australia can contribute up An intensive study of these biomass-burning events undertaken at ATARS during the early dry season in 2014 also confirmed spikes in GEM concentration that were associated with biomass burning (Mallet et al, 2016;Desservettaz et al, 2017). The distance to the fire and atmospheric dispersion, as well as vegetation type and associated mercury loading, were all identified as factors influencing the strength of these biomass-burning signals.…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 88%
“…The Australian Nuclear Science and Technology Organisation (ANSTO) began continuous atmospheric radon measurements at the site in 2012 to aid in the determination of terrestrial influence on observed air masses (Chambers et al, 2016b). In June 2014, an additional expansion took place and now continuous aerosol, reactive gas (O 3 , NO x ), and GEM measurements complement the suite of atmospheric measurements at the site (Mallet et al, 2016). This GEM dataset represents the first multiyear time series of atmospheric mercury monitoring in tropical Australia.…”
mentioning
confidence: 99%
“…List of Smoke Events Selected, Including the Start and End Dates and Times and the Duration of the Events a Distance from site was estimated using MODIS hot spot locations and HYSPLIT back trajectories. SeeMallet et al [2016] andMilic et al [2017] for more details.…”
mentioning
confidence: 99%
“…GEM recoveries from standard additions during these periods were investigated and remained within 10 % of expected values with no evident pattern throughout the day, implying the drops in observed GEM were due to natural phenomena and not a change in instrument GEM recovery. Atmospheric mercury depletion events (AMDEs) and the mechanisms behind them have been well documented in polar regions (Steffen et al, 2008), though other similar events have been observed within the mid-latitudes (Mao et al, 2008;Brunke et al, 2010;Engle et al, 2010;Moore et al, 2013;Morrison et al, 2015;Fu et al, 2016;Howard and Edwards, 2017). The mechanisms behind these mid-latitude depletion events are less clear and likely varied -with hypotheses such as chemical conversion of GEM to RM and subsequent deposition, transport of GEM-depleted air masses, or deposition of GEM from isolated atmospheric pools being offered.…”
Section: Diurnal Variationmentioning
confidence: 99%
“…NAMDEs have also been observed in the NH, in a range of ecosystems ranging from coastal to forested (Mao et al, 2008;Engle et al, 2010;Fu et al, 2016). Mao et al (2008) attributed 70 % of their observed depletion to surface deposition and Fu et al (2016) provided modelling evidence showing that stable boundary layers of height 100 m can be completely depleted of GEM due to deposition processes. The pervasiveness of NAMDEs across multiple ecosystems, and their pervasiveness throughout the ATARS time series across all seasons, suggests that this multi-hop process is widespread.…”
Section: Diurnal Variationmentioning
confidence: 99%